Run-time Adaptation of Mobile Applications using Genetic Algorithms - García Pascual, Gustavo; Pinto-Alarcón, Mónica; Fuentes-Fernández, Lidia (IEEE Press, 2013)
Mobile applications run in environments where the context is continuously changing. Therefore, it is necessary to provide support for the run-time adaptation of these applications. This support is usually achieved by middleware platforms that offer a context-aware dynamic reconfiguration service. However, the main shortcoming of existing approaches is that both the list of possible configurations and the plans to adapt the application to a new configuration are usually specified at design-time. In this paper we present an approach that allows the automatic generation at run-time of application configurations and of reconfiguration plans. Moreover, the generated configurations are optimal regarding the provided functionality and, more importantly, without exceeding the available resources (e.g. battery). This is performed by: (1) having the information about the application variability available at runtime using feature models, and (2) using an genetic algorithm that allows generating an optimal configuration at runtime. We have specified a case study and evaluated our approach, and the results show that it is efficient enough as to be used on mobile devices without introducing an excessive overhead.
Keywords: Aplicaciones informáticas; Informática móvil; Dynamic Reconfiguration